2018
DOI: 10.1111/jph.12705
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the genetic architecture of rice resistance to Xanthomonas oryzae pv. oryzae using a genomewide association study

Abstract: Bacterial blight, caused by Xanthomonas oryzae pv. oryzae (Xoo), usually causes serious rice yield loss in many countries. Rice breeders have used resistance (R) genes to control the disease but many of the resistant cultivars become susceptible few years after releasing. Identification of new R genes to Xoo is one of the main objectives in rice breeding programs. In this study, we used a genomewide association study (GWAS) to analyse the resistance against the Xoo race C1 using the Rice Diversity Panel 1 (RDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In previous studies, BB resistance QTL and candidate genes were identified from bi-parental populations, MAGIC populations and natural populations (Bandillo et al 2013 ; Chen et al 2016 ; Descalsota et al 2018 ; Dilla-Ermita et al 2017 ; Kim and Reinke 2019 ; Li et al 2018 ; Xie et al 2015 ; Zhang et al 2017a ), allowing for a comparison between loci in this study and previously reported QTL and genes. Through our use of high-density SNP markers, QTL identified in the present research were narrowed down to a small genomic region enabling cross-reference with other reported genes and QTL spanning a larger region.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In previous studies, BB resistance QTL and candidate genes were identified from bi-parental populations, MAGIC populations and natural populations (Bandillo et al 2013 ; Chen et al 2016 ; Descalsota et al 2018 ; Dilla-Ermita et al 2017 ; Kim and Reinke 2019 ; Li et al 2018 ; Xie et al 2015 ; Zhang et al 2017a ), allowing for a comparison between loci in this study and previously reported QTL and genes. Through our use of high-density SNP markers, QTL identified in the present research were narrowed down to a small genomic region enabling cross-reference with other reported genes and QTL spanning a larger region.…”
Section: Discussionmentioning
confidence: 85%
“…According to the previous studies, a region containing more than two SNPs above the significant P -value threshold in one estimated LD block were clustered as one QTL associated with BB resistance (Li et al 2018 ; Guo et al 2020 ) and the SNP with minimum P -value within each QTL was considered as the lead SNP (Zhang et al 2019 ). Those chromosomes containing more than two QTL were referred to as hotspot chromosomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rice blight (bacterial blight, BB) caused by Xanthomonas oryzae pv. oryzae (Xoo), a Gram-negative bacterial species in the Gammaproteobacteria , is one of the most destructive bacteriosis in rice farming, which may result in more than 50% yield decline ( Mew, 1987 ; Liu et al, 2014 ; Chen et al, 2016 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rice Diversity Panel 1 (RDP1), which is estimated to have an average gene diversity of 0.68 (Ali et al 2011), is a well-known open access collection of 421 diverse accessions from 79 countries (Ali et al 2011; Eizenga et al 2014). Several studies have used RDP1 to successfully identify QTLs controlling resistance to major rice diseases such as rice blast (Kang et al 2016; Mgonja et al 2016; Zhu et al 2016; Lin et al 2018), sheath blight (Chen et al 2019), and bacterial blight (Li et al 2018). However, bakanae resistance in RDP1 remains to be explored.…”
Section: Introductionmentioning
confidence: 99%